Environmental DNA reveals the Salamander Mussel Simpsonaias ambigua alive in Illinois, USA , after a century in obscurity - Sarah A. Douglass; Savanna Palmer; Ashleigh R. McCallum; Olivia P. Reves; Hayley A. Robinson; Allison J. Rutledge; Jordan H. Hartman; Eric R. Larson; Mark A. Davis (Ecology, 2025)

Stable isotopes and diet metabarcoding reveal trophic overlap between native and invasive Banded Killifish (Fundulus diaphanus) subspecies - Jordan H. Hartman; Mark A. Davis; Nicholas J. Iacaruso; Jeremy S. Tiemann; Eric R. Larson (Environmental Biology of Fishes, 2024)

Niche conservatism and spread explain introgression between native and invasive fish - Jordan H. Hartman; Joel Corush; Eric R. Larson; Jeremy S. Tiemann; Philip W. Willink; Mark A. Davis (Molecular Ecology, 2024)
Hybridisation can be an important driver of evolutionary change, but hybridisation with invasive species can have adverse effects on native biodiversity. While hybridisation has been documented across taxa, there is limited understanding of ecological factors promoting patterns of hybridisation and the spatial distribution of hybrid individuals. We combined the results of ecological niche modelling (ENM) and restriction site‐associated DNA sequencing to test theories of niche conservatism and biotic resistance on the success of invasion, admixture, and extent of introgression between native and non‐native fishes. We related Maxent predictions of habitat suitability based on the native ranges of invasive Eastern Banded Killifish ( Fundulus diaphanus diaphanus Lesueur 1817) and native Western Banded Killifish ( Fundulus diaphanus menona Jordan and Copeland 1877) to admixture indices of individual Banded Killifish. We found that Eastern Banded Killifish predominated at sites predicted as suitable from their ENM, consistent with niche conservatism. Admixed individuals were more common as Eastern Banded Killifish habitat suitability declined. We also found that Eastern Banded Killifish were most common at sites closest to the presumed source of this invasion, whereas the proportion of admixed individuals increased with distance from the source of invasion. Lastly, we found little evidence that habitat suitability for Western Banded Killifish provides biotic resistance from either displacement by, or admixture with, invasive Eastern Banded Killifish. Our study demonstrates that ENMs can inform conservation‐relevant outcomes between native and invasive taxa while emphasising the importance of protecting isolated Western Banded Killifish populations from invasive conspecifics.

Wealth and urbanization shape medium and large terrestrial mammal communities - Seth B. Magle; Mason Fidino; Heather A. Sander; Adam T. Rohnke; Kelli L. Larson; Travis Gallo; Cria A. M. Kay; Elizabeth W. Lehrer; Maureen H. Murray; Solny A. Adalsteinsson; Adam A. Ahlers; Whitney J. B. Anthonysamy; et al. (Global Change Biology, 2021)
Urban biodiversity provides critical ecosystem services and is a key component to environmentally and socially sustainable cities. However, biodiversity varies greatly within and among cities, leading to human communities with changing and unequal experiences with nature. The “luxury effect,” a hypothesis that predicts a positive correlation between wealth, typically measured by per capita income, and species richness may be one indication of these inequities. While the luxury effect is well studied for some taxa, it has rarely been investigated for mammals, which provide unique ecosystem services (e.g., biological pest control) and exhibit significant potential for negative human–wildlife interactions (e.g., nuisances or conflicts). We analyzed a large dataset of mammal detections across 20 North American cities to test whether the luxury effect is consistent for medium‐ to large‐sized terrestrial mammals across diverse urban contexts. Overall, support for the luxury effect, as indicated by per capita income, was inconsistent; we found evidence of a luxury effect in approximately half of our study cities. Species richness was, however, highly and negatively correlated with urban intensity in most cities. We thus suggest that economic factors play an important role in shaping urban mammal communities for some cities and species, but that the strongest driver of urban mammal diversity is urban intensity. To better understand the complexity of urban ecosystems, ecologists and social scientists must consider the social and political factors that drive inequitable human experiences with nature in cities.

Participation in cognitively-stimulating activities is associated with brain structure and cognitive function in preclinical Alzheimer’s disease - Stephanie A. Schultz; Jordan Larson; Jennifer Oh; Rebecca Koscik; Maritza N. Dowling; Catherine L. Gallagher; Cynthia M. Carlsson; Howard A. Rowley; Barbara B. Bendlin; Sanjay Asthana; Bruce P. Hermann; Sterling C. Johnson; et al. (Brain Imaging and Behavior, 2015)

Cardiorespiratory fitness is associated with brain structure, cognition, and mood in a middle-aged cohort at risk for Alzheimer’s disease - Elizabeth A. Boots; Stephanie A. Schultz; Jennifer M. Oh; Jordan Larson; Dorothy Edwards; Dane Cook; Rebecca L. Koscik; Maritza N. Dowling; Catherine L. Gallagher; Cynthia M. Carlsson; Howard A. Rowley; Barbara B. Bendlin; et al. (Brain Imaging and Behavior, 2015)

Cigarette smoking and risk of ovarian cancer: a pooled analysis of 21 case–control studies - Mette T. Faber; Susanne K. Kjær; Christian Dehlendorff; Jenny Chang-Claude; Klaus K. Andersen; Estrid Høgdall; Penelope M. Webb; Susan J. Jordan; Mary Anne Rossing; Jennifer A. Doherty; Galina Lurie; Pamela J. Thompson; et al. (Cancer Causes & Control, 2013)

Soil modification by invasive plants: effects on native and invasive species of mixed-grass prairies - Nicholas R. Jordan; Diane L. Larson; Sheri C. Huerd (Biological Invasions, 2008)